On the Role of Cannabinoid CB1- and μ-Opioid Receptors in Motor Impulsivity - Wiskerke, Joost; Van Mourik, Yvar; Schetters, Dustin; Schoffelmeer, Anton N.; Pattij, Tommy (Frontiers in Pharmacology, 2012)
Previous studies using a rat 5-choice serial reaction time task (5-CSRTT) have established a critical role for dopamine D2 receptors in regulating increments in motor impulsivity induced by acute administration of the psychostimulant drugs amphetamine and nicotine. Here we investigated whether cannabinoid CB1 and/or µ-opioid receptors are involved in nicotine-induced impulsivity, given recent findings indicating that both receptor systems mediate amphetamine-induced motor impulsivity. Results showed that the cannabinoid CB1 receptor antagonist SR141716A, but not the opioid receptor antagonist naloxone, reduced nicotine-induced premature responding. In contrast, SR141716A did not affect impulsivity following a challenge with the dopamine transporter inhibitor GBR 12909, a form of drug-induced impulsivity that was previously found to be dependent on µ-opioid receptor activation. Finally, unlike SR141716A and the dopamine D2 receptor antagonist eticlopride, naloxone did not affect impulsivity when the intertrial interval was lengthened from 5 to 7s, i.e. under conditions of heightened cognitive load resulting in higher levels of premature responding. Together, these findings indicate that nicotine-induced motor impulsivity is cannabinoid, but not opioid receptor-dependent. These data confirm that the endogenous cannabinoid, dopamine, and opioid systems each play important, but distinct roles in regulating motor impulsivity. The rather complex interplay between these neurotransmitter systems modulating impulsivity will be discussed in terms of the differential involvement of mesocortical and mesolimbic neurocircuitry.